Length–weight relationship and condition factor of ten cyprinid fish species from the Caspian Sea, Urmia Lake and Persian Gulf basins of Iran - Atta Mouludi-Saleh; Soheil Eagderi; Keivan Abbasi; Seyed Mohammad Salavatian (Journal of Fisheries, 2021)
In this study, the length-weight relationships (LWRs) and condition factor (K) were estimated for 1334 specimens belonging to ten species including Acanthobrama marmid, A. microlepis, A. urmianus, Romanogobio persus, Leuciscus aspius, Luciobarbus capito, L. mursa, L. caspius, Alburnus atropatenae and Petroleuciscus ulanus from the Caspian Sea, Urmia Lake and Persian Gulf basins of Iran. The total length and weight of the individuals varied from 3.4 to 84.5 cm and 0.4 to 6600 g respectively. The values of the slope parameter (b) and condition factor ranged from 2.99 – 3.38 and 0.79 – 1.25 respectively. LWRs with high correlation coefficients were calculated for all species (R2 > 0.95). Based on the results, the allometric growth pattern of the studied species were positive except for L. aspius, L. capito, L. mursa and P. ulanus. This study provides useful data regarding the LWRs and condition factor of ten fish species in Iranian inland waters that can be used in fisheries management, stock assessment and future studies.